2017
DOI: 10.1074/jbc.m117.787838
|View full text |Cite
|
Sign up to set email alerts
|

Two independent but synchronized Gβγ subunit–controlled pathways are essential for trailing-edge retraction during macrophage migration

Abstract: Chemokine-induced directional cell migration is a universal cellular mechanism and plays crucial roles in numerous biological processes, including embryonic development, immune system function, and tissue remodeling and regeneration. During the migration of a stationary cell, the cell polarizes, forms lamellipodia at the leading edge (LE), and triggers the concurrent retraction of the trailing edge (TE). During cell migration governed by inhibitory G protein (G)-coupled receptors (GPCRs), G protein βγ (Gβγ) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 85 publications
2
26
0
Order By: Relevance
“…We have demonstrated that farnesylated Gg types, including Gg9, attenuate Gbg-effectors PLCb and phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) activations, whereas geranylgeranylated Gg types enhance their signaling (Senarath et al, 2018). We also showed that endogenously expressed Gg3 in RAW cells are required for Gi pathway activation-mediated PIP3 production and PLCb activation during cell migration (Siripurapu et al, 2017;Senarath et al, 2018). In migratory cells, lamellipodia formation at the leading edge is driven by PIP3, produced as a result of Gbg-mediated PI3K activation (Kölsch et al, 2008).…”
Section: Ramifications Of Gbg Signaling In Statin-treated Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…We have demonstrated that farnesylated Gg types, including Gg9, attenuate Gbg-effectors PLCb and phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) activations, whereas geranylgeranylated Gg types enhance their signaling (Senarath et al, 2018). We also showed that endogenously expressed Gg3 in RAW cells are required for Gi pathway activation-mediated PIP3 production and PLCb activation during cell migration (Siripurapu et al, 2017;Senarath et al, 2018). In migratory cells, lamellipodia formation at the leading edge is driven by PIP3, produced as a result of Gbg-mediated PI3K activation (Kölsch et al, 2008).…”
Section: Ramifications Of Gbg Signaling In Statin-treated Cellsmentioning
confidence: 94%
“…RAW 264.7 cells incubated with either 10 mM fluvastatin, 20 mM atorvastatin, or 10 mM lovastatin for 12 hours were pretreated with the small-molecule calcium indicator fluo-4 AM (2.28 mM). Calcium imaging was performed as described previously (Siripurapu et al, 2017). After baseline, fluo-4 fluorescence was captured, endogenous c5a receptors were activated with 20 mM c5a, and fluo4 imaging was continued.…”
Section: Ramifications Of Gbg Signaling In Statin-treated Cellsmentioning
confidence: 99%
“…The Gγ dependent differential PIP3 generation in HeLa cells hints at a plausible mechanism of how Gβγ effectors are recruited to the PM and activated by PM bound fraction of HiAf-Gβγ. We recently showed that Gβγ controls PLCβ activation, induces Ca 2+ mobilization, governing the trailing edge retraction during RAW cell migration (18). Similar to PI3Kγ, PLCβ1 and PLCβ2 are also cytosolic (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Altered cell motilities are implicated in pathological processes such as immune deficiencies, lack of wound healing, tissue repair and cancer metastasis (14)(15)(16)(17). We have recently shown that Gβγ is a key regulator of inhibitory G protein (Gi) -coupled GPCR activation induced macrophage migration (18). In addition to PI3K-PIP3 signaling at the leading edge, we demonstrated that Gβγ mediated activation of PLCβ pathway is essential for macrophage migration.…”
Section: Aaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaaamentioning
confidence: 95%
See 1 more Smart Citation